Febrile urinary tract infection after pediatric kidney transplantation: a multicenter, prospective observational study - Weigel, Friederike; Tönshoff, Burkhard (Pediatric nephrology, 2016)
BackgroundFebrile urinary tract infections (fUTIs) are common after kidney transplantation (KTx); however, prospective data in a multicenter pediatric cohort are lacking. We designed a prospective registry to record data on fUTI before and after pediatric KTx.MethodsNinety-eight children (58 boys and 40 girls) ≤ 18 years from 14 mid-European centers received a kidney transplant and completed a 2-year follow-up.ResultsPosttransplant, 38.7 % of patients had at least one fUTI compared with 21.4 % before KTx (p = 0.002). Before KTx, fUTI was more frequent in patients with congenital anomalies of kidneys and urinary tract (CAKUT) vs. patients without (38 % vs. 12 %; p = 0.005). After KTx, fUTI were equally frequent in both groups (48.7 % vs. 32.2 %; p = 0.14). First fUTI posttransplant occurred earlier in boys compared with girls: median range 4 vs. 13.5 years (p = 0.002). Graft function worsened (p < 0.001) during fUTI, but no difference was recorded after 2 years. At least one recurrence of fUTI was encountered in 58 %.ConclusionThis prospective study confirms a high incidence of fUTI after pediatric KTx, which is not restricted to patients with CAKUT; fUTIs have a negative impact on graft function during the infectious episode but not on 2-year graft outcome.
Gesehen am 06.09.2019